2002
DOI: 10.1258/1357633021937433
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of screening for diabetic retinopathy

Abstract: The costs of telemedicine screening for diabetic retinopathy were examined in a trial conducted in northern Norway, involving the University Hospital of Tromsø (UHT) and the primary care centre in Alta, approximately 400 km away. In Alta, specially trained nurses examined 42 diabetic patients using a digital camera to obtain images of the retina. The images were then sent by email to an eye specialist at the UHT. A cost-minimization analysis showed that at low workloads, for example 20 patients per annum, tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 3 publications
0
38
0
Order By: Relevance
“…Teleophthalmology aims to increase accessibility to screening while reducing costs. A Norwegian study examined the costs of telemedicine screening for DR 825 . Specially trained nurses performed nonmydriatic digital retinal photography on 42 diabetic patients, and these images were then sent to an eye specialist.…”
Section: Costs Of Telemedicinementioning
confidence: 99%
“…Teleophthalmology aims to increase accessibility to screening while reducing costs. A Norwegian study examined the costs of telemedicine screening for DR 825 . Specially trained nurses performed nonmydriatic digital retinal photography on 42 diabetic patients, and these images were then sent to an eye specialist.…”
Section: Costs Of Telemedicinementioning
confidence: 99%
“…al. [11] estimated that the conventional screening costs would be between 56 $ (335 NKr) and 459 $ (2730 NKr), depending on number of patients. If the number of patients exceeds the screening capacity of the nearby hospitals, such costs will increase considerably.…”
Section: Discussionmentioning
confidence: 99%
“…In Queensland, Australia, the results from a regional survey reported that only one in three young patients with diabetes had seen an ophthalmologist in the preceding 12 months [9]. It has been suggested to use telemedicine screening in these remote areas [9][10][11][12]. A cost-effectiveness analysis from the northern part of Norway showed that the telemedicine approach was more expensive than the conventional approach when operated at a small scale, but would break even in terms of costs per patient if a minimum of 110 patients were screened [11].…”
mentioning
confidence: 99%
“…Also, implementation of most currently available telemedicine imaging systems is practically and financially difficult in the primary care setting where few patients with diabetes requiring assessment for retinopathy are evaluated on any given day. 12 A new, validated diabetic retinopathy assessment system, involving placement of a semiautomated fundus camera in the primary care environment, was designed to facilitate referral of patients with diabetic retinopathy. It is based on the DigiScope (EyeTel Imaging, Inc., Columbia, MD), 13 which is operated by existing staff in the PCP's office, to acquire digital fundus images of patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%